ЭТИЧЕСКИЕ ПОСТУЛАТЫ АСПЕКТОВ БИОЭТИКИ В РАКУРСЕ МЕДИКО-БИОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ (World Science, 2019)
Bioethics is the new starting point of philosophical thought. Its formation and development is directly related to the transformation of medical ethics as a whole. A traditional methodological tool for acquainting oneself with the scientific, socio-political and moral essence of bioethics in the modern world is an excursion into the history of the origin and stages of the development of the subject. Interest in bioethics is, first of all, an indicator of global public attention to human rights, the use of new technologies and medical experiments on people, which in turn create serious legal and moral problems in society. Today, there is a need to study theoretical and historical aspects in order to study and classify this issue. The article discusses and sets out in detail the foundations of an ethical attitude to the human person from the perspective of biomedicine.